2021
DOI: 10.3389/fcell.2021.642212
|View full text |Cite
|
Sign up to set email alerts
|

Gene Families With Stochastic Exclusive Gene Choice Underlie Cell Adhesion in Mammalian Cells

Abstract: Exclusive stochastic gene choice combines precision with diversity. This regulation enables most T-cells to express exactly one T-cell receptor isoform chosen from a large repertoire, and to react precisely against diverse antigens. Some cells express two receptor isoforms, revealing the stochastic nature of this process. A similar regulation of odorant receptors and protocadherins enable cells to recognize odors and confer individuality to cells in neuronal interaction networks, respectively. We explored whet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…A better understanding of the relationships, and in particular mechanistic basics for controlling gene-specific slopes (i.e., response variability) as well as their sensitivity to pharmacological perturbation and infection and disease state, will require further detailed investigations ( Robles-Rebollo et al, 2022 ). Nevertheless, we believe that our methodology, relying on the inference of mean-variance relationships, provides new insight into regulation of single-cell variability of innate immune signalling and will be applicable to other gene expression systems, including prominent stochastic regulation of adaptive immunity ( de la Higuera et al, 2019 ; Iakovlev et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of the relationships, and in particular mechanistic basics for controlling gene-specific slopes (i.e., response variability) as well as their sensitivity to pharmacological perturbation and infection and disease state, will require further detailed investigations ( Robles-Rebollo et al, 2022 ). Nevertheless, we believe that our methodology, relying on the inference of mean-variance relationships, provides new insight into regulation of single-cell variability of innate immune signalling and will be applicable to other gene expression systems, including prominent stochastic regulation of adaptive immunity ( de la Higuera et al, 2019 ; Iakovlev et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of temporal mRNA production in a single cell, and the overall mRNA (and protein) distribution in cellular populations, are controlled by transcriptional bursting, namely, via the modulation of burst size and burst frequency ( Raj et al, 2006 ; Suter et al, 2011 ; Molina et al, 2013 ). The innate and adaptive immune responses exhibit extreme variability at the single cell level, in comparison to other tissue systems ( Shalek et al, 2013 ; Shalek et al, 2014 ; Hagai et al, 2018 ), where only subsets of cells produce specific effector molecules, and thus are able to respond to pathogen ( Avraham et al, 2015 ; Iakovlev et al, 2021 ). This apparent level of variability poses a fundamental systems biology question; how do robust immune responses emerge from this heterogeneous transcriptional bursting process?…”
Section: Introductionmentioning
confidence: 99%
“…In the event that the upregulated gene expression level exceeded the median, it was assigned a score of 1; otherwise, it was scored 0. If the downregulated gene expression level was below the median, it was scored 1; otherwise, it was marked as 0 37,38 . This process resulted in a matrix comprising all gene scores for CDEGs.…”
Section: Methodsmentioning
confidence: 99%
“…If the downregulated gene expression level was below the median, it was scored 1; otherwise, it was marked as 0. 37,38 This process resulted in a matrix comprising all gene scores for CDEGs.…”
Section: Cdeg Gene Scores In the Training Set Samplesmentioning
confidence: 99%
“…It has also been shown to increase stringency of synaptic partnerships in other areas of the brain ( Garrett et al, 2018 ). However, a recent analysis found that mammalian DSCAM and DSCAML1, along with other members of the basigin-related family, are sometimes expressed in a mutually exclusive pattern ( Iakovlev et al, 2021 ). It is therefore possible that DSCAM genes also contribute to non-deterministic aspects of cell identity in mammals.…”
Section: Down Syndrome Cell Adhesion Moleculesmentioning
confidence: 99%